RECONSTRUCTION OF PROVIDING A MEDICAL PROFESSION SATISFACTION THAT HAS DISASTER OF PATIENT-BASED INTEREST THE VALUE OF JUSTICE - edy sumarwanto (UNISSULA, 2017)
Doctors are a noble profession. The doctor's profession requires expertise and thoroughness, because the work of a physician deals with the health and life of a person. Mistakes by doctors can result in disability or death for the patient, so doctors must work with caution. Doctors suspected of malpractice can not simply be criminalized, because no doctor has a bad faith to harm his patients, so that sanctions are imposed should be able to provide justice for doctors and patients.